0887 Should Sleep Apnea Testing be a Component of the Diagnostic Evaluation for Treatment Resistant Depression?. (12th April 2019) - McCall, William V; Benca, Ruth M; Rumble, Meredith; Case, Doug; Krystal, Andrew
Abstract: Introduction: Resistance to standard antidepressant treatment is common for major depressive disorder (MDD), as up to 50% of MDD patients have treatment-resistant depression (TRD). The presence of undetected obstructive sleep apnea (OSA) is thought to contribute to TRD. We examined the rate of unsuspected OSA in MDD outpatients. Methods: One hundred and twenty-five adults aged 18-65 years with MDD were examined either with full in-lab polysomnography (PSG), or limited home OSA testing. All participants had significant insomnia and suicidality, and were excluded for BMI >50, prior diagnosis of OSA or restless leg syndrome. The apnea hypopnea index (AHI) was calculated with a denominator of EEG total sleep time for full PSG, and with a denominator of time in bed for home OSA testing. AHI > 10 served as a diagnosis of OSA. Results: Fourteen % of subjects met diagnosis for OSA. Linear regression revealed that older age, male gender, and greater BMI were associated with higher AHI. Conclusion: OSA occurred at clinically meaningful rates in this sample of MDD patients who were otherwise not suspected to have OSA. Although the standard risk factors of age, gender and BMI were relevant in this sample, still, the patients were not suspected to have OSA. A high index of suspicion for OSA is warranted in MDD, perhaps especially in TRD. Support (If Any): Supported by NIMH MH095776, MH095780, MH95778